The Material Ethics - Qanissa Aghara (JURNAL RUPA, 2023)
This research article illustrates the artwork creation of Angki Purbandono's "Material Ethics" a series that was made during his time in jail on 2012. Angki Purbandono is a renowned Indonesian artist that actively participated in the Indonesian contemporary art scene since 1999. He is famous for implementing scanography technique for photography artworks, including "Material Ethics" series. This research is an interdisciplinary descriptive qualitative research, that includes the realm of art and social studies. This research will be based on the theories of postmodernism, especially Lyotard's notion of narrative, and Carceral Aesthetics theory. In conclusion, this research shows that "Material Ethics" series shows postmodernism tendencies through the implementation of bricolage technique. It also enhances the notion of small narratives that was iterated by Lyotard. From the perspective of Carceral Aesthetics, this artwork shows the tendency of carceral memories.